2016
DOI: 10.1590/1981-8637201600030000103009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peri-implant mucositis

Abstract: Objective The aim of this study was to evaluate the prevalence of peri-implant mucositis, as well as hygiene care around implants and the correlation between keratinized gingiva and probing depth around implants. Methods RESUMOObjetivo O objetivo desse estudo foi avaliar a prevalência de mucosite, bem como os cuidados de higiene bucal ao redor de implantes e a correlação entre a faixa de gengiva queratinizado e a profundidade de sondagem nos implantes. MétodosForam avaliados 107 implantes dentários de 24 pacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Peri-implant diseases are defined as infectiousinflammatory lesions that develop in the tissues around the implants, and are currently considered an emerging problem [1,2]. Peri-implant diseases can be classified as peri-implant mucositis and peri-implantitis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peri-implant diseases are defined as infectiousinflammatory lesions that develop in the tissues around the implants, and are currently considered an emerging problem [1,2]. Peri-implant diseases can be classified as peri-implant mucositis and peri-implantitis [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 Few studies have presented PIM prevalence rates over 70%. Henriques et al (2016) reported that 81% of implants placed at a Brazilian University were diagnosed with PIM. The average follow-up time in that study was 2.6 years.…”
Section: Introductionmentioning
confidence: 99%